Changes in Ulnar Variance after a Triangular Fibrocartilage Complex Tear - Shim, Jung-In; Im, Jin-Hyung; Lee, Joo-Yup; Kang, Han-Vit; Cho, Sung-Hyun (Journal of Wrist Surgery, 2019)
Purpose The relationship between triangular fibrocartilage complex (TFCC) tear and ulnar impaction syndrome has not been fully understood. We hypothesized that a TFCC tear could change the ulnar variance, which may be the cause of ulnar impaction syndrome.Patients and Methods A total of 72 patients who underwent TFCC foveal repair between January 2011 and June 2016 were included in this retrospective study. Among them, 44 patients diagnosed with TFCC foveal tear with distal radioulnar joint instability and no ulnar impaction syndrome underwent TFCC foveal repair only (group A) and 28 patients diagnosed with TFCC foveal tear with ulnar impaction syndrome underwent TFCC foveal repair and ulnar shortening osteotomy simultaneously (group B). We measured their ulnar variances in preoperative, postoperative, and last follow-up plain radiography. We also compared them with the ulnar variance of the contralateral (uninjured) wrist. Postoperative clinical outcomes, such as range of motions of the wrist, the visual analog scale (VAS) for pain, grip strength, and Quick Disabilities of the Arm, Shoulder, and Hand (QuickDASH) score, were assessed.Results Ulnar variance increased after TFCC tears compared with that on the uninjured side in both groups (group A: 0.98 vs. 0.52 mm, p = 0.013; group B: 2.71 vs. 2.13 mm, p = 0.001). Once the TFCC was repaired, ulnar variance decreased (group A: 0.98 to 0.01 mm, p < 0.01; group B: 2.71 to 0.64 mm, p < 0.01). However, it was increased on the last follow-up radiograph (group A: 0.01 to 0.81 mm, p < 0.01; group B: 0.64 to 1.05 mm, p = 0.004). There were no significant improvement of range of motion, except for pronation–supination motion (p = 0.04). Mean grip strength increased from 56.8 to 70.8% of the contralateral unaffected hand at the last assessment (p = 0.01). Mean VAS for pain decreased from 7.4 ± 2.5 preoperatively to 2.7 ± 2 postoperatively (p = 0.001). The QuickDASH score significantly improved from 45 to 9 (p = 0.001).Conclusion Ulnar variance may be changed after a TFCC tear. In our study, it decreased after TFCC foveal repair. However, as time went on, the ulnar variance increased again, which could be one of the causes of ulnar impaction syndrome and ulnar-sided wrist pain.Level of Evidence This is a therapeutic Level IV study.
Keywords: distal radioulnar joint; triangular fibrocartilage complex; ulnar impaction syndrome; ulnar shortening osteotomy; ulnar variance